Wieloznaczność rozwoju - Sagan, Eli (Er(r)go. Teoria - Literatura - Kultura, 2002)
Marcin Sarnek's Polish translation of an excerpt from Eli Sagan's "Human Aggression and Cultural Form" (chapter 9, 1588).